Optical Music Recognition for Scores Written in White Mensural Notation. (28th December 2009) - Tardón Tardón, Lorenzo J. Lorenzo J.; Sammartino Sammartino, Simone Simone; Barbancho Barbancho, Isabel Isabel; Gómez Gómez, Verónica Verónica; Oliver Oliver, Antonio Antonio
Abstract : An Optical Music Recognition (OMR) system especially adapted for handwritten musical scores of the XVII-th and the early XVIII-th centuries written in white mensural notation is presented. The system performs a complete sequence of analysis stages: the input is the RGB image of the score to be analyzed and, after a preprocessing that returns a black and white image with corrected rotation, the staves are processed to return a score without staff lines; then, a music symbol processing stage isolates the music symbols contained in the score and, finally, the classification process starts to obtain the transcription in a suitable electronic format so that it can be stored or played. This work will help to preserve our cultural heritage keeping the musical information of the scores in a digital format that also gives the possibility to perform and distribute the original music contained in those scores.